Rastni trendi v evropskih gozdovih - Makkonen-Spiecker, Kaisu (Gozdarski vestnik, 1999)
The authors of the article discuss the results of growth trends of European forests survey, carried out by European Forestry Institute (EFI). Survey discusses single areas of 12 European countries. Foundings are, however, the growth trends are the most positive in Germany and Switzerland. A great deal of media, which is under the impression of forest decline, had mediated the survey results to the public in sensationalistic and media needs tailored way.Only a few media had reported objectively, and were able to accept the fact that there may be processes in the forests that either rise site productivity, and therefore the growth of the woods or, on the other hand, theprocesses such as forest decline due to trees damages, that lower the forest growth. Which processes are to prevail depends on the natural sites, tree species, health condition, air pollution, type of pollution, changes of climate and a long row of other factors.
Keywords: Evropa; gozdovi; ogroženost; propadanje gozdov